Regulation and the performance of communication and information networks - Faulhaber, Gerald R. (Edward Elgar Publishing Ltd. CheltenhamGB, 2012)
Conducts positive analysis of communications policies adopted in the past and uses that analysis to deduce lessons that can guide policy makers in the future.